Cytomegalovirus‐Related Hospitalization Is Associated With Adverse Outcomes and Increased Health‐Care Resource Utilization in Inflammatory Bowel Disease. Issue 3 (March 2016) - Zhang, Cheng; Krishna, Somashekar G; Hinton, Alice; Arsenescu, Razvan; Levine, Edward J; Conwell, Darwin L
Abstract : OBJECTIVES: : Impact of cytomegalovirus (CMV)‐related hospitalization in inflammatory bowel disease (IBD) patients is unknown. The aim of this study was to determine hospital outcomes of CMV‐related hospitalization in IBD patients in a large national in‐patient administrative data set. METHODS: : This was a cross‐sectional study using data from the Nationwide In‐patient Sample database. IBD‐ and CMV‐related hospitalizations between 2003 and 2011 were identified using appropriate ICD‐9‐CM (International Classification of Diseases, Ninth Revision, Clinical Modification) codes. Impact of CMV‐related hospitalization on in‐hospital mortality, length of stay (LOS), and hospital charges were quantified. RESULTS: : CMV‐related hospitalization was associated with higher in‐hospital mortality (odds ratio (OR) 7.09, 95% confidence interval (CI) 3.38–14.85), prolonged LOS (7.77 days, P <0.0001), and more hospital charge (US66, 495, P <0.0001) in IBD patients. CONCLUSIONS: : CMV‐related hospitalization in IBD is associated with high in‐hospital mortality, prolonged LOS, and hospital care costs.